Sports Regulation in the Constitution of Azerbaijan: Right or Obligation? - Maharramov, Royal (Sports and Law: Finding a Balance Between the Game and the Rules, 2026)
This article analyzes the constitutional regulation of sport in Azerbaijan, focusing on whether sport is conceptualized as an individual right or as a state obligation. It begins with a clarification of the legal meanings of sport, right, and obligation, supported by statutory definitions and constitutional theory, particularly the notion of human dignity derived from Kantian philosophy. The study then examines the historical development of sports regulation in Azerbaijani constitutional law, demonstrating that earlier Soviet constitutions addressed sport indirectly, primarily within the framework of freedom of association and state policy. The 1995 Constitution, despite its comprehensive rights catalogue, does not explicitly recognize sport as a fundamental right, instead emphasizing state assistance in related social fields. An analysis of the Law on Physical Education and Sport and relevant Constitutional Court jurisprudence highlights the application of proportionality and equality principles in sports-related regulation. The article concludes that, in the absence of explicit constitutional recognition and sustained state support, sport cannot effectively operate as a social right.